Convergence and anchoring of yield curves in the euro area - Michael Ehrmann; Marcel Fratzscher; Refet S. Gürkaynak; Eric Swanson (European Central Bank (ECB), 2007)
We study the convergence of European bond markets and the anchoring of inflation expectations in euro area countries using high-frequency bond yield data for France, Germany, Italy and Spain. We find that Economic and Monetary Union (EMU) has led to substantial convergence in euro area sovereign bond markets in terms of interest rate levels, unconditional daily fluctuations, and conditional responses to major macroeconomic data announcements. Our findings also suggest a substantial increase in the anchoring of long-term inflation expectations since EMU, particularly for Italy and Spain, which since monetary union have seen their long-term interest rates become much lower, much less volatile, and much better anchored in response to news. Finally, the reaction of far-ahead forward interest rates to macroeconomic announcements has converged substantially across euro area countries and even been eliminated over time, thus underlining not only market integration but also the credibility that financial markets attach to monetary policy in the euro area.
Keywords: E52; E58; 330; anchoring; bond markets; convergence; credibility; EMU; euro area; monetary policy; Rentenmarkt; Rendite; Zinsstruktur; Inflationserwartung; Geldpolitik; Wirtschaftliche Konvergenz; Eurozone; EU-Staaten